Associations between indoor soundscapes, building services and window opening behaviour during the COVID-19 lockdown. (March 2022) - Torresin, Simone; Albatici, Rossano; Aletta, Francesco; Babich, Francesco; Oberman, Tin; Kang, Jian
Results of an online survey conducted during the COVID-19 lockdown among 848 home workers living in London (United Kingdom) and in Italy are reported with a focus on (1) the impacts of building services on the perception of the acoustic environment while working and relaxing at home and (2) the factors associated with window opening behaviour. The analyses showed no significant difference in soundscape appropriateness for relaxation depending on the heating, ventilation and cooling system typologies, and in soundscape appropriateness for working from home (WFH) based on the ventilation strategy. Higher soundscape appropriateness for WFH was associated with houses equipped only with radiant floors for heating in Italy and with air-cooling systems in London. In London, air systems resulted in higher perceived dominance of noise from building services compared to other systems. Overall, rooms with less dominant sounds from building services were evaluated as more appropriate for working and relaxing. The dominance of sky or buildings from the window view, outdoor noisiness, noise sensitivity, age and gender were not significantly associated with participants' window opening behaviour while WFH. Differently, participants viewing more vegetation from windows in Italy were more likely (odds ratio: 1.279) to keep the window open while WFH.